2009
DOI: 10.1002/hipo.20587
|View full text |Cite
|
Sign up to set email alerts
|

Increased hippocampal neurogenesis in the progressive stage of Alzheimer's disease phenotype in an APP/PS1 double transgenic mouse model

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease associated with senile beta-amyloid (Abeta) plaques and cognitive decline. Neurogenesis in the adult hippocampus is implicated in regulating learning and memory, and is increased in human postmortem brain of AD patients. However, little is currently known about the changes of hippocampal neurogenesis in the progression of AD. As brain tissues from patients during the progression of AD are generally not available, an amyloid precursor protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 26 publications
(36 reference statements)
10
75
0
1
Order By: Relevance
“…Although some previous reports show that functional neurogenesis is reduced in the 3xTgAD mouse models of AD (86,87), the increased proliferation reported here is consistent with data obtained either by DCX positive alone or by DCX/BrdU cell counts in a transgenic mouse model expressing human APP isoforms with the Swedish (K670N/M671L) and Indiana (V717F) mutations (88) and in other models (APP/PS1 double transgenic) (89). Interestingly, a similar increase in adult hippocampal cell proliferation (measured by multiple endogenous newborn neuron markers) was found in the subgranular zone of human subjects with AD (88).…”
Section: Discussionsupporting
confidence: 92%
“…Although some previous reports show that functional neurogenesis is reduced in the 3xTgAD mouse models of AD (86,87), the increased proliferation reported here is consistent with data obtained either by DCX positive alone or by DCX/BrdU cell counts in a transgenic mouse model expressing human APP isoforms with the Swedish (K670N/M671L) and Indiana (V717F) mutations (88) and in other models (APP/PS1 double transgenic) (89). Interestingly, a similar increase in adult hippocampal cell proliferation (measured by multiple endogenous newborn neuron markers) was found in the subgranular zone of human subjects with AD (88).…”
Section: Discussionsupporting
confidence: 92%
“…Although the concept of a reduction in hippocampal neurogenesis preceding the development of A␤ plaques may account for the onset of cognitive decline, further studies are required to pinpoint exactly where alterations in hippocampal neurogenesis occur in relation to other pathologies in the development of AD. There have also been reports of increased hippocampal neurogenesis in mouse models of AD (Ermini et al, 2008;Jin et al, 2004a;Mirochnic et al, 2009;Verdaguer et al, 2015;Yu et al, 2009). It is likely that differences in animal models, the age at which they are studied, extent of A␤ pathology and method of assessment of neurogenesis, in particular BrdU administration protocols, all affect comparisons across these studies and may account for some of the differences observed with some studies reporting reductions in neurogenesis and others reporting increases.…”
Section: Alterations In Hippocampal Neurogenesis In Ad Mouse Modelsmentioning
confidence: 99%
“…Deficits in spatial memory (Ben-Menachem-Zidon et al, 2014;Choi et al, 2014b;Iascone et al, 2013;Tapia-Rojas et al, 2016;Valero et al, 2011), spontaneous alternation (Li et al, 2015), contextual memory (Ben- MenachemZidon et al, 2014;Imbimbo et al, 2010) and recognition memory (Biscaro et al, 2012;Blanchard et al, 2010) have all been observed to occur alongside reductions in hippocampal neurogenesis. Interestingly, Yu et al (2009) report that nine month old APP + PS-1 mice are impaired in the MWM task and have increased hippocampal neurogenesis. This finding further demonstrates the complexities in studying the role of hippocampal neurogenesis in AD and determining how it integrates with declining cognitive function as the disease progresses.…”
Section: Alterations In Hippocampal Neurogenesis In Ad Mouse Modelsmentioning
confidence: 99%
“…Both the increase and decrease in neurogenesis have been observed in the brains of transgenic rodents that partly mimic AD pathology. 56,57 It has been shown that there are several possible reasons for the limited repair capacity of neurogenesis in AD. [58][59][60] First, the rate or extent of cell loss may be too great for a quantitatively significant replacement to be achieved.…”
Section: Signs Of Neurodegeneration In Oxys Ratsmentioning
confidence: 99%